THE RELATIONSHIP BETWEEN GLAUCOMA AND SERUM VITAMIN B12, FOLIC ACID LEVELS AND NUTRITION - (:unkn) unknown (CARBONE EDITORE, 2015)
Aims: To examine the relationship between diet, serum vitamin B12 and folic acid levels and glaucomatous optic neuropathy. Materials and methods: The study included 77 glaucoma patients and 40 healthy individuals as the control group. Vitamin 812 and folic acid levels in serum were Measured by chemiluminescence method. Nutrition and diet experts analyzed dietary intake vitamin B12 and folic acid levels of all individuals in the study by using a questionnaire. Results: Median and standard deviation of vitamin B12 serum levels were 231 and 135.19 in glaucoma patients. They were 272.5 and 84.54 in the control group, and the difference was statistical significant (p=0.016). Median and standard deviation of serum folic acid levels were 7.86 and 3.15 in glaucoma patients and were 6.9 and 3.1 in the control group. The difference was not statistical significant (p=0.144). Analysis of vitamin B12 and folic acid levels of glaucoma patients with serum vitamin B12 levels according to their food consumption revealed that 1 of 16 glaucoma patients had normal vitamin B12 intake, while 15 had deficient vitamin B12 intake. Dietary intake of folic acid was found to be deficient in 14 of 16 glaucoma patients. Conclusion: Determination of low serum level of vitamin B12 in 16 of 77 glaucoma patients may indicate the importance of dietary vitamin B12 intake in glaucoma patients.
Keywords: Glaucoma; vitamin B12; folic acid; nutrition; OPEN-ANGLE GLAUCOMA; OCULAR BLOOD-FLOW; PSEUDOEXFOLIATION GLAUCOMA; PLASMA HOMOCYSTEINE; RISK